Maxillary Reconstruction with Xenogeneic Bone Graft, Platelet-Rich Fibrin, and Titanium Mesh for Rehabilitation with Implants: A 5-year Follow-Up Study - Graziele Parize; Samy Tunchel; Alberto Blay; Eduardo Felippe Duailibi-Neto; Yeon Jung Kim; Debora Pallos (Case Reports in Dentistry)
Aim. Alveolar deficiency is considered one of the main limitations for placement of osseointegrated implants, as well as for their long-term success, especially in the anterior region of the maxilla. Objective. To report a clinical case of reconstruction of atrophic maxilla with deproteinized bovine bone associated with platelet-rich fibrin (PRF) and titanium mesh and to assess the linear and volumetric bone gains and rehabilitation with implants in a 5-year follow-up. Case. Patient with bone deficiency in the anterior maxilla region underwent bone reconstruction with deproteinized bovine bone associated with PRF and titanium mesh. After six months, the necessary bone height and volume were obtained for placement of implants, and the bone contour was restored in the anterior region, providing functional and aesthetic improvement. The amount of linear and volumetric bone gains was compared to baseline computed tomography scans. Three implants were placed in the grafted region, and a bone tissue sample was obtained at the time of their placement. Histological analysis showed neo-formed bone tissue in contact with the remaining particles of the biomaterial. After six months, the implants were activated, and the prosthesis was placed on the implants, which were monitored for five years. Conclusion. Implants can be placed predictably in regions with vertical and horizontal bone augmentations by using xenogeneic bone grafts associated with titanium mesh and PRF.